Childhood Glaucoma: Long-Term Outcomes of Glaucoma Drainage Device Implantation Within the First 2 Years of Life - Moritz C. Daniel (2020)
© 2019 Wolters Kluwer Health, Inc. Précis:Glaucoma drainage device (GDD) implantation within the first 2 years of life yields an overall success rate of 59.0% at 5 years. It is safe and requires a relatively low number of postoperative interventions.Purpose:The purpose of this study was to evaluate the long-term outcomes of the treatment of childhood glaucoma with GDDs within the first 2 years of life.Methods:A total of 43 children (60 eyes) having undergone GDD implantation within the first 2 years of life at Moorfields Eye Hospital between July 2005 and November 2014 were included in this retrospective case series. Kaplan-Meier survival curves were created for the evaluation of surgical success. Log-rank analysis was performed for the detection of risk factors for failure. Main outcome measures: Overall success rates at 1, 5, and 7 years after surgery. Surgical success: intraocular pressure ≥5/≤21 mm Hg, no further glaucoma surgery required, nonoccurrence of loss of perception of light or devastating complications.Results:The results are listed as follows: Median duration of follow-up was 48.0 months. Median age at surgery was 11.5 months. Seventy-three percentage of children were white. Most common types of glaucoma were primary congenital glaucoma [(PCG); 67%], glaucoma following cataract surgery (18%), and anterior segment dysgenesis (10%). Overall success rates were 93%, 59%, and 59%, respectively. There were no differences in the survival rates as a function of PCG/non-PCG, sex, and removal of intraluminal stent suture. Mean number of general anesthesia administrations during the first postoperative year was 1.8.Conclusions:GDD implantation within the first 2 years of life is effective and safe. The low number of general anesthesia administrations required during the first postoperative year could help to reduce the burden placed on children and carers. Further research is required to directly compare the efficiency of GDD implantation with other surgical options.